Impact of a synchronous prophylactic treatment of the anterior accessory saphenous vein on the recurrent varicose vein rate in patients undergoing thermal ablation of an insufficient great saphenous vein (SYNCHRONOUS-Study): study protocol for a prospective, multicentre, controlled observational study - Lorenz Uhlmann; Christine Fink; Karsten Hartmann; Thomas Mattausch; Hans-Christian Wenzel; Phillip Zollmann; Jürgen Veltman; Thomas Weiler; Guido Lengfellner; Lars Müller; Markus Stücker; Felizitas Pannier; et al. (BMJ Open)
Introduction To date, there are no prospective studies evaluating the prevention of recurrent veins by the simultaneous treatment of a sufficient anterior accessory saphenous vein (AASV) in patients undergoing endovenous laser ablation (EVLA) of an insufficient great saphenous vein (GSV). This study will provide important information about the impact of the AASV on the development of recurrent veins after EVLA of the GSV. Additionally, it will be clarified whether patients benefit from a preventive ablation of a sufficient AASV.Methods and analysis This is a multicentre, prospective, controlled, exploratory clinical study in 1150 patients with a medical indication for EVLA of a refluxing great saphenous vein. Patients will be enrolled into two study groups: in half of the patients EVLA will be performed on the insufficient GSV only. In the other half of the patients EVLA will be performed on the insufficient GSV and additionally on the sufficient AASV. Within seven study visits, patients will be followed-up over a time period of 5 years. Primary study endpoint is the recurrence rate; secondary endpoints include inter alia, complication rate, postoperative pain intensity, quality of life and patient satisfaction.Ethics and dissemination Before initiation of the study, the protocol was presented and approved by the independent ethics committee of the medical faculty of the University of Heidelberg (Ethics approval number S-596/2018). This study was prospectively registered at the German Clinical Trial Register (https://www.germanctr.de/). Research findings will be disseminated in a peer-reviewed journal and at relevant conferences.Trial registration number German Clinical Trial Registry (DRKS00015486).